Cardinal Purple for Maximilian of Pernstein. A Contribution to Aristocratic Women's Political Communication - Marek, Pavel (My University, 2018)
The aim of the study is to show what means and methods served noblewomen in the early modern period when communicating with the Papal Court. The studied issue will be analysed through the example of Marie Manrique de Lara, who at the beginning of the 1590s attempted to help her second-born son Maximilian of Pernstein to work his way up to the College of Cardinals
Kardinálský purpur pro Maxmiliána z Pernštejna. Příspěvek k politické komunikaci šlechtických žen
Keywords: political communication; Maximilian of Pernstein; gender history; cardinal's elevation; Holy See; Habsburg dynasty; family network; client relations; politická komunikace; Maxmilián z Pernštejna; gender history; kardinálská promoce; papežský dvůr; habsburská dynastie; příbuzenská síť; klientské vztahy